WhatsApp control: a new norm to succeed in LIMS adoption - Reddy, Mallikarjun Janardhan; A. S. Anand; Khajasab; Ankur Ankit (International Journal of Research in Medical Sciences, 2023)
Background: Adoption of the LIMS (laboratory information management system) serves varied purposes in the diagnostic laboratory and might take a very lengthy period for its implementation. But, without controls being put in place, it can create a barrier to the project’s execution and prevent it from being finished on time. Methods: A WhatsApp group with 22 members, including lab technicians, heads of lab sections, a billing manager, an operations assistant manager, an assistant nursing caretaker, and administrative staff, was created. The assistant operations manager posted the daily pending report status in the WhatsApp group to help the lab team ratify, correct, and complete the assignments. To track pending report closures in real-time, the WhatsApp group mediated weekly follow-ups. The laboratory services department head informed the team monthly on the project’s status. The nonparametric Wilcoxon rank test and paired student t-test were performed to compare pre and post-survey responses before and after the seven-month intervention period. Results: The non-parametric Wilcoxon rank test and paired t-test results of the post-test demonstrated that the participant’s answer had improved significantly since the pre-test. The questionnaire showed that participants liked the new WhatsApp control mechanism. The number of pending reports reduced from 4,000 to 240 in seven months, a statistically significant decrease at a p value of 0.01. This supports the newly implemented WhatsApp control. Conclusions: Based on this interventional study, WhatsApp-based controls can be employed in conjunction with more conventional ways to regulate process outcomes during LIMS adoption.